Validation of Popular Scientific Books on the Results of Morphological and Anatomical Characterization of Binjai (Mangifera caesia Jack.) - Sa'adah, Hafizatus; Ita, Ita (Bioeduca : Journal of Biology Education, 2024)
Validation is meant to be the truth of a product developed. Validation aims to determine the validity of a product, for example, in Popular Scientific Book (BIP). BIP is written in a simple and easy to understand. Contains about everyday activities that relate to the life of the community. Binjai is a typical Kalimantan plant that has benefits related to the local wisdom. This research aims to describe validation of BIP resulting from the morphology and anatomy characterization of binjai. This research method uses an EDR by Plomp that is limited to the prototype stage and using Tessmer's formative evaluation. The subject of this research is the experts and users who will evaluate BIP. The data collection technique is a questionnaire distributed to the research subjects. The validity test showed that the developed BIP was categorized as very valid with score 85.42%. Readability the development BIP is categorized very well with score 95.83%.